Thomas & friends. Engines and escapades - Allcroft, Britt; Awdry, W.; HIT Entertainment; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : Distributed by 20th Century Fox Home Entertainment, 2008)
Meet Madge, Thomas' newest friend. Adventures and surprises are around every corner, so hold on tight and watch as the Island of Sodor bustles with hilarious antics and nonstop action.
Duncan does it all -- Sir Handel in charge -- Cool truckings -- Ding-a-ling -- Skarloey storms through -- Wash behind your buffers.
English, Spanish and French tracks.
Title from container.
Created by Britt Allcroft.
Based on the stories by The Reverend W. Awdry.
Special features: Bonus episode 'Fireman Sam: fiery finale.'
Not rated.
Keywords: Thomas the Tank Engine (Fictitious character) -- Juvenile drama; Television programs for children; Video recordings for the hearing impaired; Animated television programs